Ground motion characteristics of the 2015 central Nepal (Gorkha-Dolakha) Earthquake and 2023 SE Turkey Earthquake doublets (Journal of Nepal Geological Society, 2023)
The Alpine-Himalayan orogenic belt, the well-identified seismically active region in the world, has been evidenced by the occurrence of recent two devastating earthquake doublets in 2015 in central Nepal (MW 7.8 and MW 7.3) and in 2023 in southeastern Turkey(MW 7.8 and MW 7.5). In this study, seismic ground motion characteristics of two damaging earthquakes namely the 2015 central Nepal earthquake doublet that occurred in the central Himalaya and the 2023 southeastern Turkey earthquake doublet that occurred in the eastern Mediterranean has been investigated. The observed strong-motion recordings indicate that the peak ground acceleration (PGA) values are about 152.61–154.96 cm/s2 of the 2015 central Nepal earthquake doublet at KATNP station and about 451.834–842.924 cm/s2 of the 2023 southeastern Turkey earthquake doublet at station 3137. The seismic ground motion of both the 2015 central Nepal and the 2023 SE Turkey earthquakes doublet shows that the 2015 central Nepal doublet produced much lower peak ground acceleration than the 2023 southeastern Turkey earthquake doublet.